Phosphorylated STAT5 directly facilitates parvovirus B19 DNA replication in human erythroid progenitors through interaction with the MCM complex. - Safder S Ganaie; Wei Zou; Peng Xu; Xuefeng Deng; Steve Kleiboeker; Jianming Qiu (PLoS Pathogens, 2017)
Productive infection of human parvovirus B19 (B19V) exhibits high tropism for burst forming unit erythroid (BFU-E) and colony forming unit erythroid (CFU-E) progenitor cells in human bone marrow and fetal liver. This exclusive restriction of the virus replication to human erythroid progenitor cells is partly due to the intracellular factors that are essential for viral DNA replication, including erythropoietin signaling. Efficient B19V replication also requires hypoxic conditions, which upregulate the signal transducer and activator of transcription 5 (STAT5) pathway, and phosphorylated STAT5 is essential for virus replication. In this study, our results revealed direct involvement of STAT5 in B19V DNA replication. Consensus STAT5-binding elements were identified adjacent to the NS1-binding element within the minimal origins of viral DNA replication in the B19V genome. Phosphorylated STAT5 specifically interacted with viral DNA replication origins both in vivo and in vitro, and was actively recruited within the viral DNA replication centers. Notably, STAT5 interacted with minichromosome maintenance (MCM) complex, suggesting that STAT5 directly facilitates viral DNA replication by recruiting the helicase complex of the cellular DNA replication machinery to viral DNA replication centers. The FDA-approved drug pimozide dephosphorylates STAT5, and it inhibited B19V replication in ex vivo expanded human erythroid progenitors. Our results demonstrated that pimozide could be a promising antiviral drug for treatment of B19V-related diseases.